2021
DOI: 10.1161/circheartfailure.121.008364
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Heart Failure Among Patients With and Without Severe Mental Illness and the Association With Long-Term Outcomes

Abstract: Background: Patients with severe mental illness (SMI) including schizophrenia, bipolar disorder, and severe depression have earlier onset of cardiovascular risk factors, predisposing to worse future heart failure (HF) compared with the general population. We investigated associations between the presence/absence of SMI and long-term HF outcomes. Methods: We identified patients with HF with and without SMI in the Duke University Health System from 2002 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
0
11
1
1
Order By: Relevance
“…Women were judged more harshly if they had underlying depression and were given worse Stanford Integrate Psychosocial Assessment for Transplant (SIPAT) scores and more likely to be excluded from heart transplant candidacy as a result [6 ▪ ]. However, severe mental illness was associated with worse outcomes in men after transplant not women [44 ▪ ]. Other subjective perceptions also influence healthcare providers, particularly when it comes to minority populations.…”
Section: Resultsmentioning
confidence: 99%
“…Women were judged more harshly if they had underlying depression and were given worse Stanford Integrate Psychosocial Assessment for Transplant (SIPAT) scores and more likely to be excluded from heart transplant candidacy as a result [6 ▪ ]. However, severe mental illness was associated with worse outcomes in men after transplant not women [44 ▪ ]. Other subjective perceptions also influence healthcare providers, particularly when it comes to minority populations.…”
Section: Resultsmentioning
confidence: 99%
“…[8] In particular, the manic phase of bipolar disorder exhibited the highest GLS values, in contrast to the conventional understanding of myocardial function in psychiatric conditions. [9] This deviation from expected norms raises questions about the underlying cardiac adaptations or stressors in bipolar disorder during its different phases. Such findings highlight the need for cardiac monitoring in bipolar patients, as these variations may have significant clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…bipolar disorder, and substance abuse) and adverse clinical outcomes in HF. 70,71 Thus, more studies are needed to evaluate the relationship between mental disorders and clinical outcomes in HF. Second, few studies in our review explored the effect of comorbid diseases on quality of life and self-care.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, mental disorders in our review may have been underreported. However, many studies have indicated a negative impact of psychological disturbance on outcomes in HF, 69 and some studies have suggested that there may be a significant relationship between mental disorders other than depression (eg, schizophrenia, bipolar disorder, and substance abuse) and adverse clinical outcomes in HF 70,71 . Thus, more studies are needed to evaluate the relationship between mental disorders and clinical outcomes in HF.…”
Section: Discussionmentioning
confidence: 99%